(untitled) - Mao, Keyu; Plevova, Kristina; Chen, Xi; Pabon, Laura Juliana Prieto; Poulain-Martini, Sophie; Michelet, Véronique (Comptes Rendus. Chimie, 2025)
An efficient intramolecular domino cyclization/Friedel–Crafts type transformation of N-(alkenyl)-amide-1,6-enynes has been developed under silver, gold, and platinum catalysis. The optimization of this process in the presence of silver complexes led to functionalized tri- and tetracyclic derivatives in good to excellent yields. The reaction conditions were found to be amenable with electron-donating and electron-withdrawing groups (12 polycyclic adducts). For mono- and non-substituted enynes, gold and platinum complexes were found to be efficient.